2008
DOI: 10.26754/uz.978-84-92521-41-8
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación de nuevas sondas microscópicas al estudio del magnetismo de las fases de laver RCO2

Abstract: Cualquier forma de reproducción, distribución, comunicación pública o transformación de esta obra solo puede ser realizada con la autorización de sus titulares, salvo excepción prevista por la ley. Diríjase a CEDRO (Centro Español de Derechos Reprográficos, www.cedro.org) si necesita fotocopiar o escanear algún fragmento de esta obra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 165 publications
(370 reference statements)
0
3
0
Order By: Relevance
“…As has been discussed in previous works [1,9,51], the occurrence of parimagnetism in ErCo 2 is caused by competition of interactions on the Co sublattice. In particular, the Co-Co exchange interaction is responsible for the short-range order correlations, which induce the collective reversal of the Co moments at the temperature at which the net moment of the Co magnetic sublattice crosses zero.…”
Section: Ac Magnetic Susceptibilitymentioning
confidence: 63%
“…As has been discussed in previous works [1,9,51], the occurrence of parimagnetism in ErCo 2 is caused by competition of interactions on the Co sublattice. In particular, the Co-Co exchange interaction is responsible for the short-range order correlations, which induce the collective reversal of the Co moments at the temperature at which the net moment of the Co magnetic sublattice crosses zero.…”
Section: Ac Magnetic Susceptibilitymentioning
confidence: 63%
“…The DMA data also show a very weak anomaly, seen most clearly in the data for tan δ collected at 2 Hz (figure 2), at 140 K. The weakness of the 140 K feature and strength of the one around 200 K contrasts markedly with the relative scale of the features seen at these T s in the electromagnon spectra, which may indicate variable coupling between strain and the primary order parameter at the lower-T anomaly. Resonant ultrasonic spectroscopy of BiFeO 3 from ca 5 to 1000 K will be reported elsewhere [29]. These show strong anomalies near 1 MHz at 140 K, and in this sense are complementary to the low-frequency (several Hz) DMA measurements reported here, which give strong effects near 201 K but only weak 'shoulders' at 140 K. In addition, the RUS measurements confirm a glassy viscous state of between 30 and 50 K; note that the Vogel-Fulcher freezing temperature was previously estimated by Singh et al as 29.4 K and a peak in the magnetic susceptibility found at 50 K. Kleemann et al [30] have demonstrated ageing of magnetization in this spin-glass temperature regime.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…As it has been discussed in previous works, 1,9,39 the occurrence of parimagnetism in ErCo 2 is due to a competition of interactions on the Co sublattice. In particular, the Co-Co exchange interaction is responsible for the short-range order correlations which facilitate the collective reversal of the Co moments at the temperature where the net moment of the Co magnetic sublattice crosses zero.…”
Section: B Ac Magnetic Susceptibilitymentioning
confidence: 62%